INCREASING IPS LEARNING OUTCOMES THROUGH THE APPLICATION OF CONCEPT ACHIEVEMENT AT SD KECIL CEMPAKA SARI - Nashrullah Nashrullah (Jurnal Dikdas, 2021)
This study aims to improve social studies learning outcomes through the application of the concept achievement of fourth grade students at SD Kecil Cempaka Sari, Sausu sub-district. The population of this study were all fourth grade students with a total of 12 people. The method used in this research is Classroom Action Research. In this study, there are four stages of research implementation, namely: planning, implementing actions, observing and reflecting on the results of the action. From the four stages of the study, two learning cycles were carried out. From the results of the first cycle of action, there were 7 people who had not completed and the classical completeness only reached 41.67%, so the research was continued in the second cycle, because in the first cycle it had not reached the predetermined performance indicators. In cycle II, the percentage of classical completeness increased to 91.6%. From the results of this study, it can be concluded that the use of the concept achievement model can improve social studies learning outcomes and student activities at SD Kecil Cempaka Sari.